Effects of dietary faba bean (Vicia faba L.) inclusion on carcass characteristics, meat quality, and blood biochemistry in Awassi lambs - Belal S. Obeidat; Nawras L. Al Shabuol; Linda Alyahya (Veterinary World)
Background and Aim: The search for sustainable and cost-effective protein alternatives to soybean meal in livestock diets has led to the exploration of legumes such as faba beans [FBs] (Vicia faba L.). This study investigated the effects of dietary inclusion of FBs on carcass traits, meat quality, and selected blood parameters in Awassi lambs.